A Longitudinal Analysis of Outcomes of Lupus Nephritis in an International Inception Cohort Using a Multistate Model Approach. Issue 8 (27th July 2016) - Hanly, John G.; Su, Li; Urowitz, Murray B.; Romero‐Diaz, Juanita; Gordon, Caroline; Bae, Sang‐Cheol; Bernatsky, Sasha; Clarke, Ann E.; Wallace, Daniel J.; Merrill, Joan T.; Isenberg, David A.; Rahman, Anisur; et al.
Abstract : Objective: To study bidirectional change and predictors of change in estimated glomerular filtration rate (GFR) and proteinuria in lupus nephritis (LN) using a multistate modeling approach. Methods: Patients in the Systemic Lupus International Collaborating Clinics inception cohort were classified annually into estimated GFR state 1 (>60 ml/minute), state 2 (30–60 ml/minute), or state 3 (<30 ml/minute) and estimated proteinuria state 1 (<0.25 gm/day), state 2 (0.25–3.0 gm/day), or state 3 (>3.0 gm/day), or end‐stage renal disease (ESRD) or death. Using multistate modeling, relative transition rates between states indicated improvement and deterioration. Results: Of 1, 826 lupus patients, 700 (38.3%) developed LN. During a mean ± SD follow‐up of 5.2 ± 3.5 years, the likelihood of improvement in estimated GFR and estimated proteinuria was greater than the likelihood of deterioration. After 5 years, 62% of patients initially in estimated GFR state 3 and 11% of patients initially in estimated proteinuria state 3 transitioned to ESRD. The probability of remaining in the initial states 1, 2, and 3 was 85%, 11%, and 3%, respectively, for estimated GFR and 62%, 29%, and 4%, respectively, for estimated proteinuria. Male sex predicted improvement in estimated GFR states; older age, race/ethnicity, higher estimated proteinuria state, and higher renal biopsy chronicity scores predicted deterioration. For estimated proteinuria, race/ethnicity, earlier calendar years, damage scores without renal variables, and higher renal biopsy chronicity scores predicted deterioration; male sex, presence of lupus anticoagulant, class V nephritis, and mycophenolic acid use predicted less improvement. Conclusion: In LN, the expected improvement or deterioration in renal outcomes can be estimated by multistate modeling and is preceded by identifiable risk factors. New therapeutic interventions for LN should meet or exceed these expectations.